Fertilizer Management and Nutrient Use by Sago Palm (Metroxylon Sagu) on Peat and Mineral Soils - Vincent, Adebiyi Ojo Timothy (2003)
Earlier research on the use of fertilizer nitrogen (N), phosphorus (P) and potassium (K) to enhance the growth performance of Sago Palms (Metroxylon sp.) on peat could not produce any positive result despite peat being reported to be nutrient deficient. This study was carried out with the main aim of evaluating the N, P and K fertilizer use by young sago palms grown on peat and mineral soils. The nutrient sorption study on mineral and peat soils showed that both soils interacted weakly with ammonium and potassium ions respectively. The potential buffering capacity (b-value) of the peat for ammonium and potassium ions is 6.61 and 34.09 respectively while the respective b-value of the mineral soil for the ions is 1.62 and 6.23. The mineral soil showed strong affinity for phosphate ion (P-sorption index: 1442.2; b-value for the first slope: 962.8) while the peat soil exhibited no interaction with the ion (b-value: -0.46). Evidences from the controlled experiments showed that the poor sorption ability of peat for ammonium, potassium and phosphate ions enhances the nutrient leaching and diffusion movements within the peat medium. Results from Experiment 5.1 in which the effect of soil type applied with three rates of N, P or K showed that soil type has significant effect on P uptake and the subsequent palm performance. The poor sorption ability of peat for phosphate ion caused P-toxicity in the palms while the palms grown on the mineral soil are not affected . For the palms grown on the mineral soil, leaflets P concentrations with the increasing rate of P applied are 0.112, 0.118 and 0.133% (Std. error: 0.004) and the corresponding dry matter yields are 339.3, 374.6 and 431.1g/plant (Std. error: 55.1). For the palms grown on the peat soil, leaflets P concentrations are 0.237, 0.340 and 0.403% (Std. error: 0.095) and the corresponding dry matter yields are 123.9, 41.2 and 36.3 g/plant (Std. error: 22.6). Effect of P-toxicity on peat was shown by significant decline in plant height, girth size and dry matter yield with the increasing rates of P applied. It is evident in both experiments that high rate of P application was too excessive for sago palms growing in potted peat soil ; a rate as low as 0.1g P/plant at a time was adequate.